Syntax-Sematic Interface: Translation-Based Study of Logical Form in English And Igala (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2025)
Using logical form which is a form of check theory, this paper demonstrates the syntax-semantic interface between two unrelated languages – English and Igala. A number of model examples were offered to illustrate the possible structural and semantic interactions present in the two languages. This is done with a view to show that appropriate syntactic interpretation is not limited to Indo-European languages alone or a language of wider diffusion but to also African minority languages in the Kwa family. This paper also confirms that syntactic ambivalence can be interpreted in the two languages with the help of Logical form. Studies that border on syntax and semantic interface are beneficial to translators who need to be conversant with check theory to attain correct semantic interpretation of texts.